HYDROGEOLOGY AND 13C ANALYSIS IN THE NORTHERN REGION OF MOUNT CIREMAI, KUNINGAN REGENCY, WEST JAVA - Saputra NIM: 22715305, Rudy
Mount Ciremai is one of the active volcanoes located in Kuningan Regency, West Java. Mount Ciremai has erupted four times and produced many volcanic materials which are widely distributed in Kuningan Regency (Situmorang, 1995). Some of those young volcanic materials have been considered as good groundwater aquifers. The overall objective of this study is to understand the physical and chemical characteristics of groundwater around Mount Ciremai which has become the main water resources for people in Kuningan Regency and Cirebon, to understand the genesis of groundwater around Mount Ciremai, and to understand the groundwater isotope δ13C anomaly and the pattern of groundwater flow around Gunung Ciremai. There are 52 cold springs observation points in the research area. The laboratory analysis of 21 cold springs samples has been conducted to determine the content of main and minor dissolved elements in groundwater. IRMS analysis was also performed to determine the stable isotopes δ13C of groundwater. The measured parameters of the cold springs in the research area consist of temperature (T), degree of acidity (pH), electrical conductivity (EC), total dissolved water (TDS), and discharge (Q). The Decree of the Minister of Health No. 416 (1990), argued that groundwater should meet the water quality standards, proper to be consumed and have big enough discharge. The main ion data was analysed using piper diagram to determine the type of groundwater in the study area. There are three types of groundwater facies: type I (HCO3- + CO3), type II (Ca+Mg Ã‚Â– HCO3-), and type III (Na++K+ - Cl-+SO42-). The piper diagram analysis in the anion and kation of water samples in the study area does not show any significant variation. Those types of groundwater are still dominated by bicarbonate ions contained in the water. The sources of bicarbonate ions for type I and type II in the research area are interpreted to be derived from meteoric water. The isotope value δ13C in the research area is ranged from -2.72 to -20.71 0/00. Groundwater with an isotope value of δ13C less than -10 is interpreted to have a deep groundwater flow pattern while for isotope values δ13C smaller than -10 has a shallow groundwater flow pattern. The role of geological structures is so influential that deep groundwater can come to the surface as a spring